Crystal structure of 4-methoxy-N-(piperidine-1-carbonothioyl)benzamide - Suhud K.; Hasbullah S.A.; Ahmad M.; Heng L.Y.; Kassim M.B. (International Union of Crystallography, 2024)
In the title compound, C14H18N2O2S, the piperidine ring has a chair conformation. Its mean plane is twisted with respect to the 4-methoxybenzoyl ring, with a dihedral angle of 63.0 (3). The central N-C( S)-N(H)-C( O) bridge is twisted with an N-C-N-C torsion angle of 74.8 (6). In the crystal, molecules are linked by N-H...O and C-H...O hydrogen bonds, forming chains along the c-axis direction. Adjacent chains are linked by C-H...φ interactions, forming layers parallel to the ac plane. The layers are linked by offset φ-φ interactions [intercentroid distance = 3.927 (3) Å ], forming a supramolecular three-dimensional structure.